2020
DOI: 10.21472/bjbs(2020)071501
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil quality influenced by biostimulant foliar fertilizers

Abstract: Foliar fertilization has been used as an important tool to meet the tree nutrient demand and to be an environmental beneficial with the use of little quantities. Actually modern fruit trees physiology is focused on the stimulation of plant cell development and fruit production using biostimulants. In olive trees, few products have been used for improving oil quality. For this purpose, two biostimulants products have been tested and used simple or combined with a third product rich in nitrogen. The treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Similarly, Frioni et al [58] showed beneficial effects of the seaweed extract foliar applications on fruit quality for several red grapevine cultivars over various climatic conditions (from cold to warm viticultural regions). Whereas in other studies, the authors observed different behaviours of the crops treated with biostimulant due to different climatic conditions [51,64]. In particular, Gutiérrez-Gamboa et al [64] observed that in grapevine, the seaweed applications had a differential effect on must amino acids content, which depended on the climate conditions of the season.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Frioni et al [58] showed beneficial effects of the seaweed extract foliar applications on fruit quality for several red grapevine cultivars over various climatic conditions (from cold to warm viticultural regions). Whereas in other studies, the authors observed different behaviours of the crops treated with biostimulant due to different climatic conditions [51,64]. In particular, Gutiérrez-Gamboa et al [64] observed that in grapevine, the seaweed applications had a differential effect on must amino acids content, which depended on the climate conditions of the season.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies reported the positive effects of biostimulant application on olive yield and oil quality [33,[50][51][52]. In particular, Zouari et al [51] observed that the foliar application of biostimulant could increase the oil polyphenol content during two consecutive growing seasons.…”
Section: First Experimentsmentioning
confidence: 99%
“…The treatment of olive trees, cv 'Chemlali', with two biostimulants, Alcygol (seaweed with boron) and Nectar intense (based on proteins), changed the olive oil quality profile [139]. For the Alcygol biostimulant, an increase of carotenoids and a reduction of peroxide value and total phenols was observed, while with the use of Nectar intense, the monounsaturated fatty acids (MUFAs) and carotenoids increased but the polyunsaturated fatty acids (PUFAs) decreased.…”
Section: Biostimulant Effect On Olive Fruits Oil Yield and Qualitymentioning
confidence: 99%
“…In the previous few decades as olive production increased as it is a source of essential fatty acids and antioxidants in diet of human being (Cicerale et al, 2012;Preedy and Watson, 2020). The presence of functional bioactive compounds, fatty acids and antioxidants gave an importance to olive oil hence it considered as a famous diet of Mediterranean areas people (Souilem et al, 2017;Zouari et al, 2020).…”
Section: Importance Of Olive Oilmentioning
confidence: 99%